Performance Study of Generalized Space Time Block Coded Enhanced Fully Optical Generalized Spatial Modulation System Based on Málaga Distribution Model - Yi Wang; Rui Zhou (Photonics, 2023)
This paper proposes a generalized space time block coded (GSTBC) enhanced fully optical generalized spatial modulation (EFOGSM) system based on Málaga (M) turbulent channel. GSTBC-EFOGSM adopts the hybrid concept of generalized space time block coded and optical spatial modulation to further utilize the high transmission rate of EFOGSM and the diversity advantage of GSTBC in free space optical (FSO) communication systems. Considering the combined effects of path loss, pointing error and atmospheric turbulence, the Meijer G function is used to derive the closed-form expression for the average bit error rate (ABER) of GSTBC-EFOGSM. Then, the ABER performance, data transmission rate, energy efficiency and computational complexity at the receiver of GSTBC-EFOGSM are compared with other optical spatial modulation schemes by simulation. In addition, the effects of key factors, such as data transmission rate, encoding ratio, number of photodetectors and modulation order, on the ABER performance of the system are also analyzed via simulation. Monte Carlo (MC) simulation is used to verify the correctness of the numerical simulation. The simulation results show that the GSTBC-EFOGSM system has better ABER performance and good performance gain.